Penyusunan Bahan Ajar IPA Fisika sebagai Upaya Peningkatan Literasi Sains Peserta Didik pada Tema Bunyi (UPEJ Unnes Physics Education Journal, 2019)
Science literacy began to be accommodated in Indonesia in the curriculum 2006 (KTSP) and more clearly seen in the curriculum 2013 through inquiry activity and scientific approaches. Based on the result of a comparative study conducted by OECD through PISA for children aged 15-17 years, Indonesia obtained unsatisfactory result. It was caused by the Indonesian’s low interest in reading according to UNESCO in 2012. Another thing that caused the low scientific literacy score of students was textbooks. The result of an analysis of the SMP science textbook which used in various schools in Central Java showed that the learning materials did not contain scientific literacy components. Textbooks have an important role in science learning. The learning material which used during the learning process was the learning support beside the role of the teacher. This research was a research and development that produced a product in the form of a science literacy learning material with sound as the theme. The purpose of this research was to find out the characteristics, validity and effectiveness of the learning material compiled. The assessment was conducted on grade VIII F which was chosen based on purposive sampling technique. The result showed that the preparation of physical science learning material based on science literacy could improve the ability of science literacy in the medium category. In addition, the cognitive, affective, and psychomotor learning outcomes were good.